Continuous infusion of the α7 nicotinic acetylcholine receptor agonist EVP-6124 produces no signs of tolerance at memory-enhancing doses in rats: a pharmacokinetic and behavioral study. Issue 4 (June 2015) - van Goethem, Nick P.; Prickaerts, Jos; Welty, Devin; Flood, Dorothy G.; Koenig, Gerhard
Abstract : We investigated whether the effects of acutely administered EVP-6124, an α7 nicotinic acetylcholine receptor (α7 nAChR) agonist, on cognition were maintained after 6-day continuous minipump administration. Performance in a delay-dependent forgetting test was measured in the object recognition task after single-oral doses of 0.3 or 1 mg/kg, or at plasma steady-state concentrations ( C ss ) of 0.6 or 2 ng/ml, which were similar to the efficacious plasma concentrations after single-oral dosing. The 0.3 mg/kg acute dose enhanced memory at a total plasma concentration of ∼0.3 ng/ml at 1–4 h after dosing. Continuous treatment produced total plasma C ss values of 0.48 and 1.93 ng/ml on day 6 and enhanced memory. At EVP-6124 plasma concentrations that optimally enhance memory in the object recognition task, tolerance did not develop after 6 days of continuous treatment.